2001
DOI: 10.5254/1.3547636
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Mixing Method, Microstructure and Strength of Nr:Br Blends

Abstract: Much published literature on the way in which phase morphology and filler distribution affect blend properties is contradictory or confusing. Experiments were carried out to elucidate the relationships and to determine whether the use of compatibilizers or special mixing techniques might have a beneficial effect on natural rubber:butadiene rubber (NR:BR) blend properties. NR:BR blends were prepared using both a masterbatch method and a single-stage mixing method. A cure system which gave an even distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This seems true for Akron abrasion but not for DIN abrasion. The strong interface bonding between NR and BR is well documented [27] and plays an important part in the ability of blends to withstand deformation. However, the Akron abrasion test demonstrates that the interaction is not strong enough to sustain material integrity as indicated by higher losses with MRP074 at up to 30 pphr.…”
Section: Abrasion Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…This seems true for Akron abrasion but not for DIN abrasion. The strong interface bonding between NR and BR is well documented [27] and plays an important part in the ability of blends to withstand deformation. However, the Akron abrasion test demonstrates that the interaction is not strong enough to sustain material integrity as indicated by higher losses with MRP074 at up to 30 pphr.…”
Section: Abrasion Resistancementioning
confidence: 99%
“…These factors also need to be considered when incorporating MRP074 into any rubber matrix. Clarke et al [27] concluded that a suitable mixing cycle could produce a fine textured morphology due to optimum filler dispersion. This results in blends with higher strength whereas the clustering in coarse morphology is more likely to introduce premature crack initiation and consequent early failure.…”
Section: Crescent (Propagation) Tear Strengthsmentioning
confidence: 99%
“…As a traditional rubber blend, natural rubber/polybutadiene rubber (NR/BR) blend, which is also an incompatible rubber pair, has gained great attention in both tire industry and scientific research. The effect of thermal aging and blend ratio on the physical properties, [1][2][3] the effect of additive type [4][5][6] and the influences of mixing procedures and additive incorporation sequence on the NR/BR blend properties 7,8 were investigated. However, the great challenge is how to improve compatibilisation of the rubber pair.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the processability of the masticated elastomer conditions the efficiency with which other ingredients are incorporated within the rubber matrix 1. Recent research on the mastication of NR has been dedicated to its effects on the elastomer's bulk properties2–4 and macromolecular structure,5, 6 although some have nonetheless been directed to its effects on the processability of compounded stocks under different strain amplitudes,7 or using conventional test equipment (such as rotational and capillary viscometers)8 and nonconventional processability test equipment 9. Often, some of this equipment is criticized for their low strain rates (10 to 1 s −1 ) when compared to strain rates in industrial processing equipment (10 3 to 10 4 s −1 ).…”
Section: Introductionmentioning
confidence: 99%